Manajemen Masjid dalam Meningkatkan Kualitas Jamaah Masjid Nurul Iman Cimahi - Zahrani, Isna Kamilia; Kusnawan, Aep (Tadbir: Jurnal Manajemen Dakwah, 2022)
This study aims to identify and analyze the process of management functions which include planning, organizing, implementing, and supervising. This study uses a descriptive method with a qualitative approach. The results of the research at the Nurul Iman Mosque, Jalan Hercules Raya No. 13 Complex Melong Green Garden Cimahi Selatan Cimahi City shows that, First, long-term program planning must be discussed carefully, Second, the organization of the mosque will be structured if the initial planning is in accordance with what has been determined. Third, the implementation of mosque activities will run well and there will be no obstacles if the schedule has been arranged systematically. Fourth, supervision in the mosque environment that must be considered properly and correctly.